Effect of Plasticizer on Delivery of Valsartan from Tamarind Gel Based Transdermal Film Formulation - Panda, Braja Bihari; Chatterjee, Ayan; Sahoo, Rudra Narayan; Mallick, Subrata (Indian Journal of Pharmaceutical Education and Research, 2020)
Purpose: The present investigation was undertaken to study the effect of different plasticizers on the drug delivery pattern of valsartan from tamarind gum based hydroxypropyl methylcellulose (HPMC K100) transdermal film formulation. Methods: The matrix films of valsartan were prepared by casting solvent evaporation method using triethanolamine, propylene glycol, dimethyl sulphoxide, polyethylene glycol 400 or polyethylene glycol 600 as plasticizers. Physicochemical characteristics have also been evaluated using FTIR, DSC and SEM studies. Results: Instrumental studies revealed no major drug-excipience interaction. Amorphization of drug have been noticed in all the film formulations. A significant difference of drug diffusion as well as permeation between the formulations has been observed due to the presence of different plasticizers. This study confirmed that plasticizer cotributed a major role in developing a drug delivery system in tamarind based HPMC transdermal film. Conclusion: Highest area under the curve of the drug diffusion and ex vivo permeation profiles has been assured with the PEG 600 containing film up to 24 h of study. Hence, transdermal film formulation could be designed using different plasticizer in tamarind based HPMC matrix system as per requirements.
Keywords: Valsartan; Hydrophilic plasticizer; Tamarind gum; Transdermal film; ex-vivo; permeation